Silicophytolith studies in South America and Argentina: scope and limitations for paleoenvironmental reconstruction of the marine isotope stage 3 (MIS3) - Osterrieth, Margarita (2016)
Silicophytoliths are amorphous silica biomineralizations deposited in intracellular or extracellular spaces of plant tissues. Due to their taxonomic value and their high preservation in a variety of soils and sediments, they are widely used as indicators of past plant communities. Numerous phytolith studies show the presence of past grass-dominated ecosystems in the Late Cenozoic, including changes between glacial and interglacial periods. Studies in South America are scarce, particularly those associated to the temporal interval corresponding to the Marine Isotopic Stage 3 (MIS3). A synthesis of silicophytolith studies on pedosedimentary sequences of MIS3 age in South America is herein presented and, particularly, our own work carried out in Argentina. Integrated profiles’ representatives of typical pedostratigraphic sequences from two regional geomorphological units (Mesopotamia and the Pampean Plain) were analyzed. Samples from pedostratigraphic sequences were subjected to routine analysis. Silicophytoliths were extracted after the elimination of carbonates, organic matter, and clay; and their morphologies were described under optical and scanning electron microscopes (SEMs). Profiles from both regions show the presence of conspicuous paleopedological levels, developed in the MIS3 interval. C3grasses (Pooideae and/or Panicoideae subfamilies) and, in a lesser proportion, C4grasses (Chloridoideae and/or Panicoideae subfamilies) were present in both areas. This indicates the development of mesothermal grass-dominated ecosystems, which nowadays grow mainly in warm-temperate regions. Within the MIS3, frequent climatic environmental variations during the Late Pleistocene may have led to a fluctuation in biogeographic connections between the Mesopotamian region and other parts of South America, closely linked to the Chaco-Pampean plain and, at other times, to inter-tropical regions.